How do teaching quality and pedagogical practice enhance vocational student engagement? A mixed-method classroom observation approach. Issue 6 (12th March 2020) - Zhao, Yanmin; Ko, James
Abstract : Purpose: The purpose of this paper is to investigate vocational teaching behaviours in facilitating pedagogical practice concerning students' classroom engagement. Design/methodology/approach: A mixed-method approach with quantitative classroom observations and qualitative field notes was conducted at two higher vocational institutions in Guangdong province, south of China. Sixty lesson observations were rated combining with supplementary field notes from 20 teacher participants analysed through a comparative coding process. Findings: Means of dimensions of teaching behaviours and student engagement were calculated based on taking the averages of the means of items theoretically associated with each dimension. Through thematic analysis of observational notes, vocational instructions and students' engagement in vocational learning environment were more diversified in terms of vocational teaching practice, which manifested that vocational teaching behaviours focused more on adjusting students' practical learning. Research limitations: The limitation is shown that the quantitative sample is small, yet affords greater depth of data for further discussion. Originality/value: This study develops its setting and orientation by applying the classroom observation instrument into the Chinese high vocational context and offers more in-depth insights and exploration of the characteristics of teaching practice in vocational classrooms.